Research Note—How Does Personality Matter? Relating the Five-Factor Model to Technology Acceptance and Use - Devaraj, Sarv; Easley, Robert F.; Crant, J. Michael (Information Systems Research, 2008)
The five-factor model (FFM) of personality has been used to great effect in management and psychology research to predict attitudes, cognitions, and behaviors, but has largely been ignored in the IS field. We demonstrate the potential utility of incorporating this model into IS research by using the FFM personality factors in the context of technology acceptance. We propose a dispositional perspective to understanding user attitudes and beliefs, and examine the effect of user personality—captured using the FFM's big five factors—on both the perceived usefulness of and subjective norms toward the acceptance and use of technology. Using logged usage data from 180 new users of a collaborative technology, we found general support for our hypotheses that the FFM personality dimensions can be useful predictors of users' attitudes and beliefs. We also found strong support for the relationships between intention to use and system use.